Povidone-iodine Solutions Inhibit Cell Migration and Survival of Osteoblasts, Fibroblasts, and Myoblasts. Issue 23 (1st December 2017) - Liu, James X.; Werner, Jordan A.; Buza, John A.; Kirsch, Thorsten; Zuckerman, Joseph D.; Virk, Mandeep S.
Abstract : Study Design: In vitro laboratory study. Objective: The purpose of this study was to identify the effect of dilute povidone-iodine (PVI) solutions on human osteoblast, fibroblast and myoblast cells in vitro . Summary of Background Data: Dilute PVI wound lavage has been used successfully in spine and joint arthroplasty procedures to prevent postoperative surgical site infection, but their biologic effect on host cells is largely unknown. Methods: Human primary osteoblasts, fibroblasts, and myoblasts were expanded in cell culture and subjected to various concentrations of PVI (0%, 0.001%, 0.01%, 0.1%, 0.35%, 1%) for 3 minutes. To assess the effect of PVI on cell migration, a scratch assay was performed, in which a "scratch" was made by a standard pipette tip in a cell monolayer following PVI exposure, and time to closure of the scratch was evaluated. Cell survival and proliferation was measured 48 hours post-PVI exposure using a cell viability and cytotoxicity assay. Results: Closure of the scratch defect in all cell monolayers was achieved in <24 hours in untreated controls and following exposure to PVI concentrations <0.1%. The scratch defect remained open indefinitely following exposure to PVI concentrations of ≥0.1%. PVI concentrations <0.1% did not have significant effect on survival rates compared with control for all cell types. Cells exposed to PVI ≥ 0.1% had cell survival rates of less than 6% ( P < 0.05). Conclusions: Clinically used concentration of PVI (0.35%) exerts a pronounced cytotoxic effect on osteoblasts, fibroblast, and myoblasts in vitro . Further investigation is required to systematically study the effect of PVI on tissue healing in vivo and also determine a safe and clinically potent concentration for PVI lavage. Level of Evidence: N/A